A Study on the Mechanism of Doctor Behavioral Distortion Caused by DRG/DIP Cost Control - Genshui ZHANG; Yanna MAO; Yuanni ZHANG; Baoying CHEN; Hong JIANG (Yixue yu zhexue, 2025)
The purpose of this study is to analyse the effect mechanism of the distortion of doctors' behaviour under the background of the payment reform of diagnosis-related groups (DRG) and diagnosis-intervention packet (DIP), so as to reveal the existing problems and their underlying causes in the implementation process of medical insurance payment policies. The study adoptes the purposive sampling method to select 22 respondents for interviews, and analysed and coded the interview contents to build a theoretical model of the influencing mechanism. Through the coding study, it is found that the action mechanism of alienating physician behaviour under the cost control of DRG/DIP has the following five aspects: medical cost, clinical and technical aspects, data and technology, policy and management, and physician behaviour. Overall, the distortion of physician behaviour under the DRG/DIP payment reform is comprehensively affected by multiple factors. It is recommended to improve policy publicity and support, strengthen coordination between technology and medical insurance, and formulate more reasonable evaluation and incentive mechanisms to reduce the distortion of doctors' behaviour and improve the quality of medical services.